Two or four hour [18F]FMISO-PET in HNSCC - Abolmaali, N.; Haase, R.; Koch, A.; Zips, D.; Steinbach, J.; Baumann, M.; Kotzerke, J.; Zöphel, K. (Nuklearmedizin - NuclearMedicine, 2011)
[18F]Fluoromisonidazole positron emission tomography (FMISO-PET) is a non invasive imaging technique that can assist detecting intra tumour regions of hypoxia. FMISO-PET evinces comparatively low signal-to-noise-ratio (SNR) and may be acquired dynamically or after different uptake times post injection (p. i.). The aim of this study was to identify, if static images acquired two hours (MISO2) or four hours (MISO4) p. i. reveal higher contrast. Patients, methods: As part of a prospective trial, 23 patients with cancers of the head and neck underwent [18F]fluoro deoxyglucose (FDG) PET before and during curative radiochemotherapy. Additionally, FMISO-PET studies 2 h and 4 h p. i. were done before treatment and after a mean dose of 11 Gy, 23 Gy and 57 Gy during RCT. After coregistration, a dedicated software was used to define the gross tumour volume (GTV) by FDG PET for the primary tumour. This volume was overlaid to the FMISO images and hypoxia within the GTV was determined. The contrast between hypoxia determined by MISO2 and by MISO4 was investigated and analysed with the Wilcoxon-matched-pairs test. Results: Mean SUVmax in tumours of all examinations was 2.2 (stdev: 0.4, min: 1.3, max: 3.4) after 2 h and 2.4 (stdev: 0.7, min: 1.1, max: 4.4) after 4 h. In the neck musculature the mean SUVmax was 1.5 at both time points and the mean SUVmean decreased from 1.2 after 2 h to 1.1 after 4 h, respectively. These effects resulted in significantly rising contrast ratios from MISO2 to MISO4. The differently defined contrasts revealed significantly higher values for examinations 4 h p. i. (p < 0.002). Conclusion: Data acquisition of [18F]FMISO should be done 4 h p. i. to gather the optimal contrast, preferably allowing further analysis, e. g. hypoxic sub volume definition for therapy planning.
Keywords: FMISO PET; head and neck cancer; tumour-tomuscle-ratio; contrast-to-noise-ratio; bio-imaging; radiotherapy treatment planning